2015
DOI: 10.1055/s-0035-1545779
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between Visual Acuity and Microperimetry in AMD Patients: Visual Acuity Appears as an Inadequate Parameter to Test Macular Function

Abstract: More than a third of the AMD patients had a bad or very bad microperimetry performance in parallel with a good visual acuity. Microperimetry is a valuable tool to assess and follow real macular function in AMD patients when visual acuity alone can be misleading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
0
11
2
Order By: Relevance
“…MAC-VA and contrast sensitivity both showed a stronger relationship with the subscales of the IVI in the overall cohort than BCVA. This is of special relevance because poor contrast sensitivity has been shown to be sensitive in discriminating early stages of AMD 34,37 . Furthermore, in previous studies contrast sensitivity was a factor impacting VRQoL of AMD patients: Roh and colleagues 38 demonstrated that contrast sensitivity was an important factor affecting VRQoL in patients with vision impairment due to bilateral advanced AMD.…”
Section: Discussionmentioning
confidence: 99%
“…MAC-VA and contrast sensitivity both showed a stronger relationship with the subscales of the IVI in the overall cohort than BCVA. This is of special relevance because poor contrast sensitivity has been shown to be sensitive in discriminating early stages of AMD 34,37 . Furthermore, in previous studies contrast sensitivity was a factor impacting VRQoL of AMD patients: Roh and colleagues 38 demonstrated that contrast sensitivity was an important factor affecting VRQoL in patients with vision impairment due to bilateral advanced AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the well-known limitations of using VA to characterize early functional deficits or quantify disease progression, VA remains the most widely accepted and used metric in evaluating visual function in AMD. To better assess visual function in AMD, various alternative metrics of functional outcome have been investigated, including dark adaptation [11], microperimetry [12][13][14], multifocal ERG [15], photo-stress recovery time [16], cone-mediated flicker sensitivity [17], photopic or scotopic light sensitivity [18,19], the Moorfields Acuity Charts [20] and contrast sensitivity [21][22][23]. Among these, contrast sensitivity (1) seems to correlate better with subjective visual impairment and visionrelated quality of life compared to VA [24][25][26][27], (2) may be affected earlier in the course of neurodegenerative disorders [28][29][30] and (3) may detect more subtle changes in visual function [24,31,32].…”
Section: The Value Of Contrast Sensitivity Testing In Amdmentioning
confidence: 99%
“…The functional deficit under reduced luminance and/or contrast has been well documented in patients with early and intermediate AMD [14,15] using a number of different functional assessments such as low luminance visual acuity (LLVA) [8,14,[16][17][18], visual acuity (VA) measurements with the Moorfields Vanishing Optotypes Acuity Chart (MAC), which employs high-pass filtered letters [19], contrast sensitivity tests [20][21][22][23]15,24,16,25], and fundus-controlled perimetry [12,[26][27][28]9,9,29]. Combinations of any of these visual function tests might further increase sensitivity to detect changes in visual function in particular in early stages of AMD.…”
Section: Introductionmentioning
confidence: 99%